Tanggung Jawab Hukum Pelaku Usaha Laundry Terhadap Kerusakan Pakaian Berdasarkan Nota Laundry Sebagai Bukti Perjanjian Jasa - Fridayanthi, Putu Pande Nathasya; Rama, Bagus Gede Ari; Budiana, I Nyoman; Nandari, Ni Putu Sawitri (Consensus : Jurnal Ilmu Hukum, 2025)
This study aims to analyze the legal responsibility of laundry service providers for damage or loss of consumer clothing, as evidenced by the laundry receipt as proof of the service agreement. The receipt serves as written evidence containing the agreement between the service provider and the consumer. The research uses a normative legal method, with primary legal sources such as the Civil Code (KUHPerdata) and the Consumer Protection Law (UUPK), along with secondary and tertiary sources. The analysis is conducted descriptively by comparing the applicable legal provisions. The findings show that the legal responsibility of laundry service providers arises from the service agreement, as stated in Article 1239 of the Civil Code and the principle of unlawful acts in Article 1365. Providers are obligated to compensate if proven negligent, in accordance with Article 19 of the UUPK. The application of the principles of justice and consumer protection forms the basis for the laundry service agreement, ensuring consumer rights are protected.